杜牧“‘秋’意象诗”研究 = Research on Du Mu’s autumn imagery poems - 林宛仪 Lim, Wan Yi (2012)
以“‘秋’意象”来抒发个人感情、将之融入于诗篇，在整个中国古典诗歌文学的脉络里不胜枚举。而每每提到“‘秋’意象”，人们不经意就会联想到悲伤。这能说是与“‘秋’意象诗”的整个发展脉络的源头有关，也能归结为古代秋天时的民间习俗文化导致这样的印象。杜牧虽然身处于晚唐时期，一个政局逐渐走向没落的年代，同时他又面对着弟弟的眼疾，却依然能够写出另一面的秋天，形成了一个不一样的“‘秋’意象诗”。本文将厘清‘秋’意象诗”与“悲秋诗”的关系，以及对“‘秋’意象诗”下一个定义。并通过文本细读来分析出杜牧“‘秋’意象诗”除了“悲”之外还拥有的其它感情倾向的作品。同时，也将详细的统计出杜牧“‘秋’意象诗”中常用的“秋”意象群是那一些，来发掘出属于他个人此类诗的风格和特色。再通过对比手法，将杜牧独特的“‘秋’意象诗”对应先唐和唐代相似的诗人作品，以便看出杜牧唯有的人格魅力和有别于人的思想心境，进而从理解其诗到了解其人。In the history of Chinese classical poetry, it is prevalent to use “Autumn Imagery” as a mean to express personal feeling and to integrate such feeling into the poetry.Very often when “Autumn Imagery” is mentioned, it gives an impression for people to link it with “Grief”. The cause for this figurative language can be traced back how the development of “Autumn Imagery’s Poems” first started and could also be attributed to the past folk’s culture and customs, which were carried out during the autumn period. Du Mu, a poet from the late Tang Dynasty, despite living in a declining political condition and struggling with his younger brother’s illness, was able to portray a positive vibe for poems related to Autumn, thus forming a new style for “Autumn Imagery’s Poems”.In this thesis, the relationship between “Autumn Imagery’s Poems” and “Grief Autumn Imagery’s Poems” will be explored. Definition for the “Autumn Imagery’s Poems” will also be clarified. Close reading will be used to uncover the emotions between the lines in Du Mu’s poems that may contain feelings other than grief. This thesis would also compute the various repetition usage of certain “Autumn Imagery” in Du Mu’s work, which forms the uniqueness in his poetries. Next, through comparison of works having similar emotion conveyance before the Tang Dynasty and works from the Tang Dynasty with Du Mu’s poetry, this is in hope to discover the unparalleled characters of the poet through understanding his poems.